Kontekstualisasi Hadis-Hadis Berambisi Menjadi Pemimpin - Tubagus Muhammad Syukron (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2019)
Contestation of the election of both heads of regions in Indonesia as a democracy of Pancasila, as happened in Serang city indicate that there is an attempt to ask for the position of a head of regional office to the people as the highest sovereign. In fact, in view of the Prophet's hadiths, asking for a position more ambitious to become a leader is prohibited. This raises a problem for the people of Indonesia, the largest Muslim country in the world, because there is a conflict between the norms of state law and religious norms. With regard to this, raises the following question: 1. How is the phenomenon of leader election in Serang city? 2. How does the analysis of hadiths ambitious to become leaders? 3. How does contextualization of hadiths of ambitiously becoming leaders against the process of electing leaders in the city of Serang? In answering the problem, the author used a mixed method between library research and field research by applying contextual analysis of Hadith Syuhudi Ismail theory which is based on the theory of Yūsuf Qarḍawi. Contestation of the election of both heads of regions in Indonesia as a democracy of Pancasila, as happened in Serang city indicate that there is an attempt to ask for the position of a head of regional office to the people as the highest sovereign. In fact, in view of the Prophet's hadiths, asking for a position more ambitious to become a leader is prohibited. This raises a problem for the people of Indonesia, the largest Muslim country in the world, because there is a conflict between the norms of state law and religious norms. With regard to this, raises the following question: 1. How is the phenomenon of leader election in Serang city? 2. How does the analysis of hadiths ambitious to become leaders? 3. How does contextualization of hadiths of ambitiously becoming leaders against the process of electing leaders in the city of Serang? In answering the problem, the author used a mixed method between library research and field research by applying contextual analysis of Hadith Syuhudi Ismail theory which is based on the theory of Yūsuf Qarḍawi. This study aims: 1. To describe the phenomenon of leader election in Serang city, 2. To understand the analysis of hadiths ambitious to become leaders and 3. To understand the contextualization of hadiths of ambitiously becoming leaders against the process of electing leaders in the city of Serang. The results of this study indicate that legal norms accompanied by phenomenon in the election of mayor and vice mayor of Serang 2018 are not contradictory to the result of contextual analysis of the hadiths ambitious on becoming leader as long as there is a real public good reason, bringing a good impact if occupied by the party requesting the position, the offer or the possibility of vacancies that can be taken with the purpose of common good with the ability and ability to carry out the mandate of the position well and not in the framework of pride.